Genetic diversity of the domestic pigeon (Columba livia) in Lorica, Colombia using genes that encode plumage colour - Causil Vargas, Luis Alfonso (2016)
The aim of this study was to evaluate the genetic diversity of populations of domestic pigeons (Columba livia) in Lorica, Colombia using genes that encode plumage color. Random sampling were made in six colonies between November and December 2015. Through urban excursions, direct observation and photographic records, 356 pigeons were studied. Autosomal markers that encode plumage coloration and design were used: Grizzle (G), Spread (S), Checker (C), and sex-linked locus Ash-Red (B). The genetic parameters allele frequencies, genetic diversity, Hardy-Weinberg equilibrium and population structure were calculated by PopGene 1.31, genetic structure and genetic distance by FSTAT v.2.9.3.2 and the dendrogram was made using the program MEGA 5. Spread and Checker markers were the most frequent, while Ash-Red marker presented the lowest values. Low genetic differentiation was obtained among populations and high gene flow and therefore, it is assumed absence of inbreeding. Besides, an excess of heterozygotes and absence of Hardy-Weinberg equilibrium was observed, and possible natural selection for the Spread marker was evident.